Anesthetic efficacy of 4% articaine buccal infiltration in the urgency treatment of mandibular molars with symptomatic irreversible pulpitis: a randomized clinical trial (Research, Society and Development, 2021)
The aim of this study was to evaluate the anesthetic efficacy of the 4% articaine by the buccal infiltration technique (BI) after inferior alveolar nerve block (IANB) with 2% mepivacaine, both with 1:100,000 epinephrine, in the urgency treatment of mandibular molars with symptomatic irreversible pulpitis (SIP). This was a prospective study, with a randomized, blinded, controlled parallel clinical trial experimental design. Thirty patients diagnosed with SIP were randomly assigned, and the control group (G1) received the IANB with 1.8 mL of mepivacaine while the experimental group (G2) also received a supplemental BI with 1.8 mL of articaine. To evaluate the anesthetic efficacy, in addition to lip numbness test, the electric pulp testing (EPT) was used. Additionally, a visual analogue scale verified the presence of pain. Two-way ANOVA and Chi-square tests were applied at a significance level of 5%. There was a reduction in pain perception after the two techniques (p